Cell‐ and developmental stage‐specific Dicer1 ablation in the lung epithelium models cystic pleuropulmonary blastoma. Issue 1 (20th January 2015) - Wagh, Purnima K; Gardner, Margaret A; Ma, Xiaolan; Callahan, Melissa; Shannon, John M; Wert, Susan E; Messinger, Yoav H; Dehner, Louis P; Hill, D Ashley; Wikenheiser‐Brokamp, Kathryn A
Abstract Inherited syndromes provide unique opportunities to identify key regulatory mechanisms governing human disease. We previously identified germline loss‐of‐function DICER1 mutations in a human syndrome defined by the childhood lung neoplasm pleuropulmonary blastoma (PPB), which arises during lung development. DICER1 regulates many biological processes critical in development and disease pathogenesis. Significant challenges in defining the role of DICER1 in human disease are identifying cause–effect relationships and generating manipulatable systems that model the complexity of organ development and disease pathogenesis. Here we report the generation of a murine model for PPB and demonstrate that precise temporal and cell type‐specific Dicer1 ablation is necessary and sufficient for the development of cystic lungs that histologically and phenotypically model PPB. Dicer1 ablation in the distal airway epithelium during early stages of lung development resulted in a cystic lung phenotype indistinguishable from PPB, whereas DICER1 function was not required for development of the proximal airway epithelium or during later stages of organogenesis. Mechanistic studies demonstrate that Dicer1 loss results in epithelial cell death, followed by cystic airway dilatation accompanied by epithelial and mesenchymal proliferation. These studies define precise temporal and epithelial cell type‐specific DICER1 functions in the developing lung and demonstrate that loss of these DICER1 functions is sufficient for the development of cystic PPB. These results also provide evidence that PPB arise through a novel mechanism of non‐cell‐autonomous tumour initiation, in which the genetic abnormality initiating the neoplasm does not occur in the cells that ultimately transform, but rather occurs in a benign‐appearing epithelial cell component that predisposes underlying mesenchymal cells to malignant transformation. Copyright © 2014 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.